Dor lombar aguda em adolescentes do ensino médio de uma cidade do sul do Brasil: prevalência e fatores associados - Onofrio, Antonio Carlos (2010)
The low back pain is a condition that affect 70-80% of adult population, at least once for the life. Recently, it was observed that low back pain in children and adolescents is a complaint as common as that verified in adults. The aim of this study was to investigate the prevalence of acute low back pain (ALBP) and associated factors, in adolescents of urban high school of Southern Brazilian city. A high school-based cross-sectional study was realized including 1233 students aged 14-19 years. The acute low back pain (ALBP) was evaluated by means of two questions. The outcome was LBP in the last 30 days. The prevalence of ALBP was 13.7%. The non-white skin students, which moved walking to the school, showed a higher prevalence of ALBP. The prevalence of ALBP is relatively high. Further studies with followup until adult age are indispensable for investigate whether physical cumulative load upon lumbar spine (for example, duration/transport, schoolbags and improper school furniture) during adolescence, may concur for development of ALBP in the adult stage